2022
DOI: 10.1002/fsn3.2903
|View full text |Cite
|
Sign up to set email alerts
|

Effect of steaming on chemical composition of Mediterranean mussel (Mytilus galloprovincialis): Evaluation of potential risk associated with human consumption

Abstract: Steaming process is the most popular method for cooking mussels worldwide. The effect of this cooking process on some toxic (Cd, Ni, Pb), essential (Cr, Cu, Fe, Mn, Zn) elements, minerals (Na, K, Ca, Mg), total lipids, and fatty acid profiles in the Mediterranean mussels (Mytilus galloprovincialis) harvested from the Black Sea was studied. Different approaches to assess the benefits and risks (n‐6/n‐3, PUFA/SFA, AI, TI, h/H, EDI, THQ, HI, TR, and HQEFA) were employed. In general, steaming process significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Another parameter used to know the quality of dietary lipids is the ratio of polyunsaturated fatty acids to saturated fatty acids (PUFA/SFA). Given that the Ministry of Health in 2004 recommended a minimum level for the PUFA/SFA ratio of 0.45 [24], all samples analyzed seemed to retain a PUFA/SFA ratio above the recommended level even after processing, in particular for canned tuna pate (F6) that showed the significantly higher value (3.89±0.87) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another parameter used to know the quality of dietary lipids is the ratio of polyunsaturated fatty acids to saturated fatty acids (PUFA/SFA). Given that the Ministry of Health in 2004 recommended a minimum level for the PUFA/SFA ratio of 0.45 [24], all samples analyzed seemed to retain a PUFA/SFA ratio above the recommended level even after processing, in particular for canned tuna pate (F6) that showed the significantly higher value (3.89±0.87) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…It is essential to observe the n-6/n-3 ratio as an index of the nutritional quality of marine lipids. A low intake of this ratio, usually less than one, in the daily diet allows for a preventive role against certain disease [24].…”
Section: Resultsmentioning
confidence: 99%
“…Heavy metals are important aquatic pollutants with non-biodegradable and bioaccumulation properties, high toxicity, and long-time persistence. Numerous studies showed that contamination of the food chain by heavy metals can cause a number of health problems to humans such as erythrocyte and testicular damages, cancer, cardiovascular and skin disease, infertility and brain damage [ [15] , [16] , [17] , [18] ] . To limit the potential impact of these pollutants on human health, organizations such as the European Union (EU), the United States Environmental Protection Agency (USEPA) have established maximum limits for Pb, Cd, Hg, Cr and As in fish.…”
Section: Introductionmentioning
confidence: 99%
“…Mussel flesh is well-known for its nourishing value, resulting mainly from the presence of n-3 PUFAs such as eicosapentaenoic acid (EPA; C20:5 n-3) and docosahexaenoic acid (DHA, C22:6 n-3). Several studies report that PUFAs contribute most to the total FA profile of M. galloprovincialis , in the range of 38–67% of total FAs [ 3 , 4 , 5 , 6 , 7 , 8 ]. This is due to the diet habit of mussels that, as they are a filter-feeding animal, consists mainly of microalgae (e.g., diatoms, flagellates) [ 9 ], which are recognized as the main source of n-3 PUFAs in the marine environment [ 10 ].…”
Section: Introductionmentioning
confidence: 99%